Mystical Contemplation and Other Ways of the Cognition of God According to Saint John of the Cross - Niziński, Rafał Sergiusz (Verbum Vitae, 2025)
This philosophical article analyzes the direction of changes in human knowledge of God under the influence of mystical contemplation in the teachings of Saint John of the Cross. The introductory part features the specificity of various types of knowledge of God: based on the beauty of nature, metaphysical analysis of the world, and faith. This serves as the backdrop for showing mystical contemplation, its nature, and the goal it pursues. The author makes a thorough analysis of the character of transformations in knowledge of God (including faith) under the influence of mystical contemplation. This idea is emphasized by John of the Cross. Yet, it is not well-developed. Conclusion: contemplation makes it possible for a man to free himself from thinking about God in worldly categories, in particular from categories of the anthropomorphic nature, because the aim of mystical contemplation is to prepare the human mind to see God after death.